Geomagnetic Pc3 pulsations during the total solar eclipse on Aug 11, 1999 - Střeštík, Jaroslav; Prikner, K
The solar eclipse on August 11, 1999, observed in the region covered by many geomagnetic observatories, has offered a unique opportunity to look for an effect of the eclipse on geomagnetic pulsations. The pulsation activity digital data have been taken from Budkov Observatory in the Czech Republic (in the X component only), from observatories in Germany (Niemegk, Fürstenfeldbruck, Bad Bergzabern), in Hungary (Nagycenk), and for comparison in South Africa (Hermanus, conjugate-point station), and in Finland (Sodankylä, far from the eclipse zone). At all these stations the field in all three component has been recorded. The pulsation amplitudes in the X component exhibit a long-term minimum near the time of the eclipse. Spectral analysis of selected short intervals confirmed this decrease and also revealed a decrease of the average pulsation period during the eclipse. Such a change in the amplitude or in the period was not observed outside of the eclipse interval or in other days. Investigation in some narrower frequency bands showed that the maximal decrease occurred in the 15-20 s band. All these changes can be found in records from all the stations near the eclipse totality belt, also in records at the conjugate-point station, where no eclipse occurred. No signature has been found in records at the station situated far from the eclipse zone. J. Střeštík a K. Prikner. Obsahuje bibliografii